2009
DOI: 10.1124/jpet.108.147793
|View full text |Cite
|
Sign up to set email alerts
|

Role of 5-Hydroxytryptamine2CReceptors in Ca2+-Dependent Ethanol Potentiation of GABA Release onto Ventral Tegmental Area Dopamine Neurons

Abstract: Activation of ventral tegmental area (VTA)-dopaminergic (DA) neurons by ethanol has been implicated in the rewarding and reinforcing actions of ethanol. GABAergic transmission is thought to play an important role in regulating the activity of DA neurons. We have reported previously that ethanol enhances GABA release onto VTA-DA neurons in a brain slice preparation. Because intraterminal Ca 2ϩ levels regulate neurotransmitter release, we investigated the roles of Ca 2ϩ -dependent mechanisms in ethanol-induced e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
68
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(77 citation statements)
references
References 40 publications
8
68
1
Order By: Relevance
“…The effects were reversible, concentration-dependent, and reproducible in the same neuron. This inhibition by EtOH is consistent with our previous observations (Xiao and Ye, 2008); but facilitation was reported in some other studies (Theile et al, 2008(Theile et al, , 2009Xiao and Ye, 2008). The VTA DA neurons in our previous study probably were located in the p-VTA, because we selected neurons stringently by such characteristics as disinhibition by MOR agonist, inhibition by 100 nM quinpirole, broad action potentials (half-width Ͼ1.2 ms), and expression of I h (Xiao et al, 2007;Xiao and Ye, 2008).…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…The effects were reversible, concentration-dependent, and reproducible in the same neuron. This inhibition by EtOH is consistent with our previous observations (Xiao and Ye, 2008); but facilitation was reported in some other studies (Theile et al, 2008(Theile et al, , 2009Xiao and Ye, 2008). The VTA DA neurons in our previous study probably were located in the p-VTA, because we selected neurons stringently by such characteristics as disinhibition by MOR agonist, inhibition by 100 nM quinpirole, broad action potentials (half-width Ͼ1.2 ms), and expression of I h (Xiao et al, 2007;Xiao and Ye, 2008).…”
Section: Discussionsupporting
confidence: 82%
“…4). A similar effect was reported by Theile et al (2008Theile et al ( , 2009). It is note- jpet.aspetjournals.org worthy that those investigators reported EtOH-induced excitation of DA neurons with increased GABA release, suggesting that the EtOH-induced excitation of VTA DA neurons could also be mediated by other cellular mechanisms, including direct excitation (Brodie et al, 1999;Appel et al, 2003;Okamoto et al, 2006).…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations